Development of a CinQASE-Based LMS Moodle to Enhance Digital Learning Engagement and Critical Thinking Skills in Work and Energy Concept - Hunaidah M; Amiruddin Takda; Luh Sukariasih; Md Asri bin Ngadi; Wa Rati (Universitas Syiah Kuala, 2025)
Physics learning in secondary schools has not been optimal in fostering critical thinking skills because the concepts are abstract and conventional methods are still dominant. The integration of the CinQASE (Collaborative in Questioning, Analyzing, Synthesizing, Evaluation) model with the Moodle learning management system (LMS) has the potential to provide interactive learning that strengthens digital learning engagement (DLE) and students' critical thinking skills (CTS). Therefore, this study aims to develop a Moodle SMS based on the CinQASE model for work and energy material to improve DLE and critical thinking skills. The research used the 4D development model, which includes the define, design, develop, and disseminate stages, with instruments in the form of validation sheets, teacher and student response questionnaires, critical thinking tests, and DLE activity analysis covering the indicators of questioning, analyzing, synthesizing, evaluating, and discipline. The results showed an expert validation score of 3.72 (highly valid), teacher response of 87% (very practical), and student response of 85% (very practical). The effectiveness test showed an increase in DLE from moderate to high and very high, as well as critical thinking skills with an N-Gain of 0.58 (moderate-high category). Thus, the Moodle LMS based on the CinQASE model for work and energy material is declared valid, practical, and effective as a learning medium to support 21st-century skills